The Role of the Extracellular Matrix in Cancer Stemness - Nallanthighal, Sameera; Heiserman, James Patrick; Cheon, Dong-Joo (Frontiers in Cell and Developmental Biology, 2019)
As our understanding of cancer cell biology progresses, it has become clear that tumors are a heterogenous mixture of different cell populations, some of which contain so called “cancer stem cells” (CSCs). Hallmarks of CSCs include self-renewing capability, tumor-initiating capacity and chemoresistance. The extracellular matrix (ECM), a major structural component of the tumor microenvironment, is a highly dynamic structure and increasing evidence suggests that ECM proteins establish a physical and biochemical niche for CSCs. In cancer, abnormal ECM dynamics occur due to disrupted balance between ECM synthesis and secretion and altered expression of matrix-remodeling enzymes. Tumor-derived ECM is biochemically distinct in its composition and is stiffer compared to normal ECM. In this review, we will provide a brief overview of how different components of the ECM modulate CSC properties then discuss how physical, mechanical, and biochemical cues from the ECM drive cancer stemness. Given the fact that current CSC targeting therapies face many challenges, a better understanding of CSC-ECM interactions will be crucial to identify more effective therapeutic strategies to eliminate CSCs.